2016
DOI: 10.1097/bpo.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Femur Stress Fractures in Children With Osteogenesis Imperfecta and Intramedullary Rods on Long-term Intravenous Pamidronate Therapy

Abstract: In this report, we describe 6 children with osteogenesis imperfecta with unusual stress femoral fractures. All children were on long-term cyclic pamidronate treatment. All fractures occurred without trauma or with minimal trauma and were located in the subtrochanteric or the diaphyseal regions of the femur over preexisting intramedullary rods. These fractures have very similar features to the reported minimal trauma atypical femoral fractures in adults on long-term bisphosphonate treatment. These fractures rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…In this series, 14/16 femoral fractures in the bisphosphonate-treated cohort occurred within the subtrochanteric location, in contrast to a widespread fracture pattern in the historical controls [5]. Hegazy et al reported a series of 6 bisphosphonate-treated children with OI who sustained minimally traumatic subtrochanteric and diaphyseal femoral fractures over preexisting intramedullary rods [4], and Vasanwala et al similarly reported an adolescent OI patient with recurrent, atraumatic femoral fractures following bisphosphonate treatment [6]. The contribution of the underlying collagen defect in the development of femoral fractures in these series is unknown, and to our knowledge there have been no reports of subtrochanteric femoral fractures in non-OI children treated with bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series, 14/16 femoral fractures in the bisphosphonate-treated cohort occurred within the subtrochanteric location, in contrast to a widespread fracture pattern in the historical controls [5]. Hegazy et al reported a series of 6 bisphosphonate-treated children with OI who sustained minimally traumatic subtrochanteric and diaphyseal femoral fractures over preexisting intramedullary rods [4], and Vasanwala et al similarly reported an adolescent OI patient with recurrent, atraumatic femoral fractures following bisphosphonate treatment [6]. The contribution of the underlying collagen defect in the development of femoral fractures in these series is unknown, and to our knowledge there have been no reports of subtrochanteric femoral fractures in non-OI children treated with bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%
“…Case series of children with osteogenesis imperfecta (OI), a disorder of bone fragility due to abnormalities in type I collagen, report a potential association between bisphosphonate treatment and proximal femoral fractures [46]. To date, there have been no reports of AFFs in children or adolescents without primary collagen defects.…”
Section: Introductionmentioning
confidence: 99%
“…Some Authors describe this type of fractures as a pediatric variant of atypical femoral fracture seen in adults with prolonged bisphosphonates use (21). It seems to be an influence of bisphosphonates effect on that type of bone.…”
Section: Discussionmentioning
confidence: 99%
“…[66][67][68] It raises questions about oversuppression of bone remodeling and its contribution to microdamage accumulation and increased bone fragility. 64,69 Hegazy et al 70 reported the occurrence of unusual femoral stress fractures in six children with OI on long-term pamidronate therapy. These fractures occurred around intramedullary rods in the subtrochanteric or diaphyseal regions of the femur and were caused by no or minimal trauma, similar to the atypical femoral fractures previously described in adults with osteoporosis on long-term BP therapy and with suppression of bone turnover.…”
mentioning
confidence: 99%